Short-Term Effects of a Resistance Training Program Using Elastic Tubing in Patients with Heart Disease - Neves Silva, João Pedro Lucas; Sá Ferreira, Tamara Iasmin de; Cavalleri, Gabriela Côrtes; da Cruz, Mayara Moura Alves [UNESP]; Galindo, Bianca Pinhal; Silva, Natália Turri da; Alencar Silva, Bruna Spolador de [UNESP]; Leite, Marceli Rocha [UNESP]; Figueira Freire, Ana Paula Coelho; Ramos, Ercy Mara Cipulo [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Pacagnelli, Francis Lopes (Sociedade Brasileira de Cardiologia, 2021)
Background: Resistance training is effective in cardiac rehabilitation; however, it is conventionally performed using free weights or machines, which can pose logistic challenges to patients with restricted mobility. For its ease of access and cost-effectiveness, elastic tubing is a particularly appealing alternative, but it remains underutilized for this purpose. Objective: To evaluate muscle strength, functional capacity, aerobic capacity, and quality of life in patients with heart disease in phase II of cardiovascular rehabilitation after a resistance training intervention based solely on elastic tubing. Methods: Thirteen patients with heart disease (age 63.33±10.80 years) trained with elastic tubing twice weekly for 6 weeks, with progressive load increase every 15 days. The following muscle groups were evaluated and trained: shoulder abductors and flexors, elbow flexors, and knee flexors and extensors. Muscle strength was evaluated using a dynamometer; functional capacity, with a 6-minute walk test and cardiopulmonary exercise test; and quality of life, using the SF-36 questionnaire. Data normality was assessed using the Shapiro-Wilk test. The paired Student’s t-test was used for comparisons before and after training, at a significance level of<5%.Results: There were significant differences in muscle strength (except for elbow flexion) and functional capacity (485.5 ± 123.3 vs 578.7 ± 110.5; p=0.0399) after the intervention. No statistical differences were found in cardiorespiratory fitness or quality of life. Conclusions: Short-term resistance training with elastic tubing improved peripheral muscle strength and functional capacity in patients with heart disease, and should be encouraged for this population. (Int J Cardiovasc Sci. 2021; 34(2):149-156)
Keywords: Cardiac Rehabilitation; Cardiovascular Diseases; Elastic Tubing; Exercise; Functional Residual Capacity; Muscle Strength Dynamometer; Resistance Training